Metachromatic leukodystrophy: Case study in a child-adolescent patient (Research, Society and Development, 2025)
Metachromatic leukodystrophy (MLD) is a rare autosomal recessive disorder affecting the white matter of the nervous system, caused by mutations in the ARSA gene, which encodes the enzyme arylsulfatase A. This condition leads to progressive loss of motor, cognitive, and sensory functions. The objective of this study is to present a qualitative analysis, of descriptive and exploratory nature, on MLD, primarily based on a clinical case study of a child-adolescent patient, complemented by a literature review. The research addresses genetic aspects, early diagnosis, clinical and therapeutic implications, as well as the main challenges faced in the management of the disease. Articles were selected from PubMed, Scielo, and Google Scholar, focusing on clinical progression and available therapies, along with interviews with the patient’s family and analysis of laboratory and imaging exams. The study aims to clarify the difficulties faced by patients and families, providing relevant data to improve diagnostic and treatment strategies. The case analysis, given the patient’s severe and irreversible prognosis, highlights the clinical complexity and psychosocial impact of juvenile MLD, emphasizing the need for early diagnosis and multidisciplinary follow-up. Despite advances in gene therapy and stem cell transplantation, current management remains limited, underscoring the importance of research to expand therapeutic options and improve patient quality of life. This study involves human research and was approved by the ethics committee under the Certificate of Presentation and Ethical Appreciation (CAAE): 87542425.0.0000.5539.